Evaluation Of The Antioxidant Activity Of Lotion Containing Ethanolic Extract Of Matoa Leaves (Pometia Pinnata J.R.Forst, & G.Forst.) - Mei Vita Rachma Pertiwi; Anna Fitriawati; Annie Rahmatillah (International Journal of Health Engineering and Technology, 2026)
Skin exposure to environmental stress produces free radicals and ROS that accelerate aging and skin damage, while antioxidant Lotions from natural extracts such as Matoa leaves (Pometia pinnata) offer protection. This experimental study aimed to evaluate the antioxidant activity of ethanol extracts, the effect of concentration (0.5-6%) on the physical quality of Lotions, and the DPPH scavenging ability of the final Lotion. The population of all Matoa leaf extract Lotion formulations; a sample of 2 kg of fresh leaves from Matesih, Karanganyar was purposively selected. Instruments included a UV-Vis spectrophotometer (517 nm), a Brookfield viscometer, a pH meter; SPSS 28.0 was analyzed by ANOVA, regression for IC50. The extract was very potent (IC50 43.07 ppm) containing flavonoids, alkaloids, saponins, tannins; All Lotions met the standards (homogeneous, pH 5.22-6.34, viscosity 10,100-12,740 cP, spreadability 5-6.5 cm), FV (6%) was optimal (IC50 66.30 ppm, strong). High concentrations increased inhibition but increased viscosity, decreased spreadability (p<0.05). The findings confirm that Matoa Lotion is effective for herbal skin care; further in vivo and stability testing is recommended.